Impact of Tourist Satisfaction Attributes on Behaviour of Sharing Tourism Experiece on Social Media - suwitho, suwitho; Mustika, Hindah; Pradhani, Fastha Aulia (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2023)
Tourist satisfaction is an emotion that is felt by visitors when they there are in a place, in this case a tourism place. The satisfaction felt by visitors makes certain behaviours, which in this case share information using social media. This objective study is examines and analyzes the predictors of tourist satisfaction and tourist engagement on the behaviour of sharing tourism experience on social media. Methode: quantitative research with analysis technique. Results all variables influence can be acceptable and positive impact. Novelty in this study is the existence of tourist engagement that is able to make something unique because both the visitor and the place visited have an emotional engagement. Implication of results that with social media so we can easy to share experience and for destination as a promotion place, communication with prospective customer and discussion. Keywords : Attraction; Engagement; Satisfaction; Social Media.